Tinjauan Hukum Ekonomi Syariah Terhadap Jual Beli Ayam Hutan Hasil Buruan dengan Senapan Angin - Nanda Anggelina Putri; Rohmat Rohmat; Susi Nurkholidah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The growing needs of humans have led to the utilization of natural resources as an economic asset, one of which is the hunting and selling of wild jungle fowl. In Islam, hunting (ash-shaid) is permitted as long as it adheres to the principles of Sharia. Islamic commercial transactions are based on the fiqh muamalah principle that all transactions are originally permissible (al-ibahah) unless there is specific evidence that prohibits them. This study aims to examine the practice of buying and selling hunted jungle fowl using air rifles in Bogatama Village, Penawartama District, Tulang Bawang Regency, and to analyze it from the perspective of Islamic economic law. The research uses a qualitative field research method, with data collected through observation, interviews, and documentation. The findings indicate several problems, such as doubts regarding the lawfulness of the hunted animal due to the hunter forgetting to recite Basmallah before shooting, or the animal dying from blunt force impact before slaughtering. These issues create elements of syubhat (doubt) and gharar (uncertainty) in the transaction, and violate the requirements for a valid Islamic sale. Therefore, such transactions are deemed invalid and should be avoided in Islamic economic practice.